2019
DOI: 10.1155/2019/9698727
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Cnidium officinale Extracts on Postoperative, Neuropathic, and Menopausal Pain in Rat Models

Abstract: Cnidium officinale, widely cultivated in East Asia, has been reported to exhibit pharmacological efficacy in various disorders. However, little has been reported on its role as a pain killer. In this study, we reveal that the C. officinale extract (COE) has great efficacy as a novel analgesic in various in vivo pain models. Administration of COE attenuated hypersensitivity in all postoperative, neuropathic, and menopausal pain models. Decreased hyperalgesia was confirmed by a mechanical withdrawal threshold as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, Cnidium officinale is traditionally used in Korea to attenuate pain and increase stamina [ 90 ]. Postoperative, neuropathic, and menopausal pain models confirmed that C. officinale extracts attenuate hypersensitivity [ 91 ]. Further, in the rat spared nerve injury model, C. officinale inhibited the induction of the proinflammatory cytokines and calpain-3 in dorsal root ganglion neurons, which may be due to its CGA and ferulic acid contents.…”
Section: Effects Of Chlorogenic Acid In Inflammatory and Neuropathic mentioning
confidence: 99%
“…For example, Cnidium officinale is traditionally used in Korea to attenuate pain and increase stamina [ 90 ]. Postoperative, neuropathic, and menopausal pain models confirmed that C. officinale extracts attenuate hypersensitivity [ 91 ]. Further, in the rat spared nerve injury model, C. officinale inhibited the induction of the proinflammatory cytokines and calpain-3 in dorsal root ganglion neurons, which may be due to its CGA and ferulic acid contents.…”
Section: Effects Of Chlorogenic Acid In Inflammatory and Neuropathic mentioning
confidence: 99%
“…Cinnamate is also known as ferulic acid [ 40 ]. Ferulic acid (an active compound from COE) inhibited the DRG inflammatory response in a rat model of nerve injury [ 41 ]. However, the potential molecular mechanisms of palmitic acid and cinnamate in LDHs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The relative mRNA levels were calculated from the obtained Ct values according to the ΔΔCt method. The Ct values were normalized to elongation factor 1α (EF) mRNA, 24) which is encoded by a house-keeping gene and used as an internal control. The normalized mRNA lev-…”
Section: Purification Of Constituents From the Rhizome Of Cnidium Omentioning
confidence: 99%